Awareness of age-related gains and losses as moderators of daily stress reactivity in middle- and older-adulthood - Wilton-Harding, Bethany; Weber, Nathan; Windsor, Tim D. (Frontiers in Psychiatry, 2022)
Objectives: Associations between awareness of one’s own ageing and well-being have received increasing attention in the field of gerontology over the last decade. The current study examines how between-person differences and within-person fluctuations of awareness of age-related change (AARC) relate to daily negative affect and vitality. Of key interest was the extent to which fluctuations in AARC moderated reactivity to stressor exposure. We predicted that higher positive perceptions of ageing (AARC-gains) would buffer the relationship between daily stressors and negative affect/vitality. Conversely, we expected that higher negative perceptions (AARC-losses) may exacerbate the relationship between daily stressors and the outcome variables. Method: Data were collected from a community-based sample of 152 Australian adults aged 53-86 (M = 69.18, SD = 5.73). For 10 consecutive days, participants completed surveys on their smartphones measuring daily stressors, AARC, and affect (positive and negative). Bayesian hierarchical linear models were used to examine whether AARC-gains and AARC-losses moderated within-person associations of daily stressors and affect (i.e., stress reactivity). Results: At the between-person level, higher AARC-gains was associated with lower negative affect and higher vitality, whereas those reporting higher AARC-losses scored higher on negative affect and lower on vitality. Within-person variables revealed that on days when AARC-gains was higher and AARC-losses was lower, this corresponded with lower negative affect and higher vitality. There was no evidence in support of individual moderating effects of within-person AARC-losses or within-person AARC-gains on stress reactivity. A trend was evident in support of a three-way WP Stress severity × WP AARC-gains × WP AARC-losses interaction in the prediction of negative affect, indicating that on days when AARC-losses was higher, the association of stress severity with negative affect was weaker if AARC-gains was higher. Follow-up analyses modelling quadratic stress severity revealed a trend suggesting an interaction of within-person stress severity and within-person AARC-losses. Discussion: Results indicate that both individual differences and short-term fluctuations in AARC are associated with daily negative affect and vitality. The results provided qualified support for a possible protective role of AARC-gains in the context of stress reactivity.